2016
DOI: 10.1002/2016jc011705
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of nearshore wave interference

Abstract: Wave focusing of energetic swell fields can result in small‐scale variations associated with coherent interference that can be important for nearshore circulation and beach dynamics. However, coherent interference is difficult to measure with conventional in situ instruments and is not accounted for in operational wave models. As a result, such effects are generally ignored. In this work, we analyze X‐band radar observations collected at Ocean Beach, San Francisco using a Wigner‐Ville or coupled‐mode spectrum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Effects of the wave coherence on the wave setup and extreme wave runup values are important, because of their effects on the morphological changes (Dalrymple & Lanan, 1976). Moreover, wave setup and runup can also be used as efficient measures of wave coherence in field experiments when using an array of wave gauges for the wave coherence recording seems impractical (Smit et al., 2016). Overall, wave coherence can potentially affect many nearshore processes and can deviate them from the analytical solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of the wave coherence on the wave setup and extreme wave runup values are important, because of their effects on the morphological changes (Dalrymple & Lanan, 1976). Moreover, wave setup and runup can also be used as efficient measures of wave coherence in field experiments when using an array of wave gauges for the wave coherence recording seems impractical (Smit et al., 2016). Overall, wave coherence can potentially affect many nearshore processes and can deviate them from the analytical solutions.…”
Section: Discussionmentioning
confidence: 99%
“…If both wave trains have the same period, for instance due to focusing on some bathymetric feature that generates a coherent bidirectional wave system, the interference waves do present a spatially periodical stationary pattern. This fact is well described by Smit et al (2016), who used X-band radar observations collected at Ocean Beach, San Francisco, and succeeded in identifying coherent interference of noncollinear waves in the nearshore area during the incidence of long-period swell, propagating over offshore shoals.…”
Section: Shoaling and Refractionmentioning
confidence: 65%
“…The spatial variation of Hs in cross wave ( x) direction is apparent in Figure c. A spatial scale related to coherent interference, λ, can be calculated according to Smit et al (), where λ=2πfalse|normalΔk12xfalse|1 and normalΔk12x is the wavenumber difference of two primary wave components (i.e., N=2 in equation ). The red shadings represent the one standard deviation of Hs in spatial domain of λ, and the observations lie within this range.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a few studies demonstrating the significance of the coherent interference for wave statistics over coastal bathymetry. A series of studies by Smit and Janssen (2013) and Smit et al (2016) have demonstrated that the smaller-scale variability of observed wave height can be well explained by the effect of coherent interference over submarine canyons off the La Jolla, CA, USA, and the San Francisco bar at Ocean Beach, CA, USA. We show here that a coherent wavefield is generated over the continental shelf, and coherent interference is the missing piece of the puzzle for understanding the modulation of local wave statistics and the formation of the large-amplitude waves.…”
Section: Introductionmentioning
confidence: 99%